Learning Experience of Students Using the Learning Management System: User’s Perspective on the Use of Moodle in the University of Jordan - Ahmad Althunibat; Wael Alzyadat; Ibrahim Almarashdeh; Mutasem Alsmadi; Aoun Othman Al Shawabkeh; Anmar Abuhamdah; Malek Alzaqebah (Advances in Human-Computer Interaction)
This study aimed to evaluate the effectiveness of Moodle LMS as an alternative delivery mode for education, particularly in the higher education system of Jordan, which has not been evaluated before. The research is based on Moore’s transactional distance learning theory, which considers interactions among students, instructors, and course material, as well as personal characteristics of students. The study included 50 participants who have taken courses on Moodle LMS at the University of Jordan. Both interviews and research surveys were conducted to gather in-depth perceptions and analysis of the participants’ experiences with Moodle LMS. The findings suggest that Moodle LMS was an effective alternative study tool during the COVID-19 pandemic and the user-friendly course design enhanced the user experience of using Moodle LMS. Participants also provided suggestions to optimize the system for better integration in the University of Jordan. Fixing Moodle LMS based on the recommendations of the study participants will significantly improve the learning experience of students. This study contributes to the advancement of the state of the art by evaluating the effectiveness of Moodle LMS in the higher education system of Jordan and providing recommendations for improvement.